THE SGR 1806-20 MAGNETAR SIGNATURE ON THE EARTH'S MAGNETIC FIELD - Mandea M.; Balasis G. (My University, 2006)
SGRs denote 'soft γ-ray repeaters', a small class of slowly spinning neutron stars with strong magnetic fields. On 2004 December 27, a giant flare was detected from magnetar SGR 1806-20. The initial spike was followed by a hard-X-ray tail persisting for 380 s with a modulation period of 7.56 s. This event has received considerable attention, particularly in the astrophysics area. Its relevance to the geophysics community lies in the importance of investigating the effects of such an event on the near-Earth electromagnetic environment. However, the signature of a magnetar flare on the geomagnetic field has not previously been investigated. Here, by applying wavelet analysis to the high-resolution magnetic data provided by the CHAMP satellite, a modulated signal with a period of 7.5 s over the duration of the giant flare appears in the observed data. Moreover, this event was detected by the energetic ion counters onboard the DEMETER satellite. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: GEOMAGNETIC FIELD; MAGNETAR; WAVELET ANALYSIS